Prevalence of periodontitis in an adult population from an urban area in North Italy: findings from a cross‐sectional population‐based epidemiological survey. (25th June 2015) - Aimetti, Mario; Perotto, Stefano; Castiglione, Anna; Mariani, Giulia M.; Ferrarotti, Francesco; Romano, Federica
Abstract Aim There is a paucity of up‐to‐date data regarding prevalence and risk indicators of periodontitis in Italy. Therefore, the aim of this study was to evaluate the prevalence of periodontitis and its risk indicators among adults from an urban area in North Italy. Material and Methods This cross‐sectional survey used a stratified two‐stage probability sampling method to draw a representative sample of the adult population of the city of Turin. About 1600 individuals, 20–75 years old, were randomly selected and 736 subjects agreed to participate (47% of the sampled subjects). Clinical parameters were assessed using a full‐mouth protocol. Logistic models were applied to assess associations between periodontitis and its putative risk indicators. Age was included as restricted cubic spline. Results Based on CDC/AAP case definition, the prevalence estimates of severe and moderate periodontitis were 34.94% (95% CI: 31.23–38.74) and 40.78% (95% CI: 36.89–44.79). The probability of periodontitis increased in smokers (adjusted OR 2.06, 95% IC: 1.26–3.37, p = 0.004) and with age but leveled off in the 50+ year‐old group (p < 0.001). Conclusion Periodontitis was highly prevalent in the Turin population. The present data will enable development of appropriate public health programs and allocation of resources.